Derivative as a Form of Insurance on Oil Price: A Case Study on British Airway - Wang, Hongfei (2007)
Abstract Over the past ten years, the increasing price of jet fuel is putting constant pressure on the airline industry. Since the jet fuel cost is the second largest operating expenditure in the airlines sector, even a small increase in the fuel price would lead a significant of expenditure on the operating cost. This paper tends to exam the use of financial derivatives to hedge against the adverse oil price change and it effectiveness. To further illustrate this point, a case study of BA will be used and help to explain how hedge works so that makes BA better off. In addition, it also highlights the incentives behind the use of financial derivatives for risk management strategy by companies. Furthermore, the comparative advantage of hedging strategy among other methods is also discussed. Our research indicates that, by implementing financial derivatives, the company's cash flow would be much more stable compare with leaving oil price unhedged. Finally, this study provides the area for further research, which focuses on the comparison of financial derivatives with other risk management strategy such as insurance.